Metabolic and transcriptomic signatures of rice floral organs reveal sugar starvation as a factor in reproductive failure under heat and drought stress. (19th May 2015) - Li, Xia; Lawas, Lovely M. F.; Malo, Richard; Glaubitz, Ulrike; Erban, Alexander; Mauleon, Ramil; Heuer, Sigrid; Zuther, Ellen; Kopka, Joachim; Hincha, Dirk K.; Jagadish, Krishna S. V.
Abstract Heat and drought stress are projected to become major challenges to sustain rice (Oryza sativa L.) yields with global climate change. Both stresses lead to yield losses when they coincide with flowering. A significant knowledge gap exists in the mechanistic understanding of the responses of rice floral organs that determine reproductive success under stress. Our work connects the metabolomic and transcriptomic changes in anthers, pistils before pollination and pollinated pistils in a heat‐tolerant (N22) and a heat‐sensitive (Moroberekan) cultivar. Systematic analysis of the floral organs revealed contrasts in metabolic profiles across anthers and pistils. Constitutive metabolic markers were identified that can define reproductive success in rice under stress. Six out of nine candidate metabolites identified by intersection analysis of stressed anthers were differentially accumulated in N22 compared with Moroberekan under non‐stress conditions. Sugar metabolism was identified to be the crucial metabolic and transcriptional component that differentiated floral organ tolerance or susceptibility to stress. While susceptible Moroberekan specifically showed high expression of the Carbon Starved Anthers (CSA) gene under combined heat and drought, tolerant N22 responded with high expression of genes encoding a sugar transporter (MST8) and a cell wall invertase (INV4) as markers of high sink strength.